Five people you meet in heaven - Albom, Mitch; Singer, Erik (New York. Hyperion Audiobooks. Prince Frederick, MD. Distributed by Recorded Books, 2003)
A novel that explores the unexpected connections between listeners' lives and the idea that heaven is more than a place.
In container (17 cm.).
Title from container.
"Unabridged Fiction"--Container.
"Featuring an exclusive interview with the author"--Container.
Compact disc.
Read by Erik Singer.
Keywords: Accident victims; Amusement parks; Amusement rides; Future life; Older men; Heaven; Death; Audiobooks; Psychological fiction